The Norfolk Ridge seamounts: Eocene–Miocene volcanoes near Zealandia's rifted continental margin. Issue 3 (3rd April 2021) - Mortimer, N.; Patriat, M.; Gans, P. B.; Agranier, A.; Chazot, G.; Collot, J.; Crundwell, M. P.; Durance, P. M. J.; Campbell, H. J.; Etienne, S.
Abstract: New age and geochemical data are used to investigate the origin of a ∼670 km-long line of eight seamount volcanoes along the western side of the Norfolk Ridge between New Caledonia and New Zealand. Altered lavas and limestones were dredged from three volcanoes during the 2015 Volcanic Evolution of South Pacific Arcs cruise of N/O l'Atalante, so a total of four, including the northernmost and southernmost, have now been directly sampled and analysed. Dating of lava and volcanic breccia clasts by Ar–Ar methods gives north-to-south ages from these sites of 31.3 ± 0.6, 33 ± 5, 21.5 ± 1.0 and 26.3 ± 0.1 Ma. These ages, along with supporting stratigraphic data on a fifth seamount from IODP borehole U1507, provisionally refute the hypotheses that the seamounts represent a southward-younging, age-progressive, intraplate volcanic chain on the Australian Plate or a subduction-related chain of restricted age range. Geochemically, the upper Eocene to lower Miocene lavas have alkaline and subalkaline basaltic compositions, and some could be shoshonitic. The location of the volcanoes along the western side of the Norfolk Ridge suggests an origin related to late Eocene and early Miocene melting near an intracontinental lithosphere–asthenosphere step. Involvement of a deep slab in petrogenesis is also possible. KEY POINTS: Eight seamounts form a line along the Norfolk Ridge. Dating and geochemistry indicate the seamount line is not a hotspot track. A rift-related origin, possibly with influence by subduction, is proposed.